Principles of Insect Morphology - Snodgrass, R. E. (Robert E.), 1875-1962 (Book collections on Project MUSE., 1993)
This classic text, first published in 1935, is once again available. Still the standard reference in the English language, Principles of Insect Morphology is considered the author's masterpiece. A talented artist as well as one of the leading entomologists of his day, Robert E. Snodgrass produced a wealth of publications that display an accuracy and precision still unsurpassed. The 19 chapters in this volume cover each group of insect organs and their associated structures, at the same time providing a coherent morphological view of their fundamental nature and apparent evolution. To accomplish this aim, Snodgrass compares insect organs with those of other arthropods. Each chapter concludes with a glossary of terms. The 319 multipart illustrations are an invaluable source of information and have never been duplicated. This edition includes a new foreword by George Eickwort, Professor of Entomology at Cornell University, which relates the book to today's courses in insect morphology. Republication of this textbook will provide another generation of students with an essential foundation for their studies in entomology.